LEVEL OF EFFECTIVENESS OF BLENDED LEARNING IN HISTORY LEARNING - Yuliantoro Yuliantoro; Supentri Supentri (LPM Universitas Pasundan, 2022)
Continuity of the learning process important for Keep going going on in order what to be destination education in a country this could achieved according to the statutory mandate that is educate life nation. So our all attempted look for proper formulation in usage method teaching Up like this. One of the learning models that can applied through based media use technology is a blended learning model. Learning blended learning is a environment designed learning with unite learning stare advance (face to face) with purposeful online learning for increase results study participant educate. Method use Approach use method quantitative description, in collection data source through questionnaires and interviews as well as study literacy reference journals and books that discuss implementation learning blended learning. Destination from results study this is a analysis simple to level effectiveness blended learning in learning history. Based on results according to criteria evaluation that results this can taken conclusion that implementation learning history in a manner blended learning can walk good so that combined implementation learning conventional and modern with technology present need cultivated because give challenges and skills students and lecturers in the learning process in the lectures. Blended learning is one approach to be one solutive solution because it really helps in continuity learning in institutions education . This also happens _ in learning campuses that apply blended learning. The role of digital based materials at first only used as crutch, will but now already changed Becomes Theory always important involved in learning good in a manner stare advance or online. With so that blended learning already run in learning on campus is solution best moment this, so past learning very giving positive impact in continuity learning on campus.